Central District Office Leadership for Diversity and Equity: Constraints and Opportunities for Policy Intermediaries. Issue 4 (July 2017) - Mattheis, Allison
This article reports the findings of a multiyear investigation of school district central office directors of diversity and equity in Minnesota, who play an important role in school desegregation/integration policy implementation. Ethnographic and survey data were collected to examine a range of leadership activities and perspectives in communities across the state that received state funding for integration programming. In this article, I present findings that illustrate the role of integration leaders as boundary-spanning policy intermediaries who navigate competing frames of meaning about the purpose and value of diversity in learning environments. Learning from these school district leaders' focus on educational equity in the context of changing demographics offers opportunities to address local community needs more directly.